CURRENT ASPECTS OF ENVIRONMENTAL REGULATIONS AND INTERVENTIONS IN EUROPE - RESEARCH FOCUS ON HUMAN HEALTH - Carmen-Mariana DIACONU; Alexandru TRIFU; Gabriel-Ionuț PLAVAN; Alin CIOBÎCĂ; Sabina Ioana COJOCARU (Journal of Applied Life Sciences and Environment)
The article focuses on a synthetic presentation of environmental legislation and policies at national and European level, based on the analysis of government strategies that aim to improve living standards through education starting from an early level, through the implementation of waste management resulting from industrial and domestic activities, through the modernization of the rural environment as a result of the financing of water supply, access programme to alternative energy and specifically gas.